Motivation and Agribusiness Entrepreneurial Intention among Generation Z at Tanah Laut State Polytechnic - Ardi Kurniawan; Khalid Al Hadring Smith; M Bastian; Faisal Basyir; Kevin Tanjung (Economics and Digital Business Review, 2026)
Z Generation is a generation whose main characteristic is being accustomed to technology. Likewise in the choice of entrepreneurial motivation. Generally, Gen Z prefers entrepreneurship to express self-actualization and the abilities they have. The research is included in quantitative research with a correlational approach. The population and sample are students of Tanah Laut Polytechnic majoring in Tax Accounting, Accounting, Agroindustry and Agro-Industrial Product Development. Data collection through questionnaires and analysis using Pearson correlation. Results show that motivation of Z Generation entrepreneurial is high category and has an impact on agribusiness entrepreneur intention which is also high. The results concluded that there was significantly relationship bet ween motivation and agribusiness entrepreneur intention.